Motor neglect: implications for movement and rehabilitation following stroke. - Punt, T; Riddoch, M (2006)
PURPOSE: The syndrome of unilateral neglect following stroke is associated with poor outcome and presents significant challenges to those providing therapy for affected individuals. In contrast to a number of reviews which have recently appeared in therapy and rehabilitation journals relating to sensory aspects of neglect, this review focuses on 'motor neglect'. SEARCH STRATEGY: We searched the clinical and scientific literature for papers concerning motor neglect. The search included the databases Web of Science, Pubmed and Cinahl, primarily using the term 'motor neglect'. There was also a large degree of secondary searching involved. DISCUSSION: Motor neglect refers to the under-utilization of a limb opposite a brain lesion that cannot be fully explained by primary sensory and motor deficits. The paper discusses classical descriptions of motor neglect and highlights the difficulties in disentangling motor neglect from hemiparesis. The related problem of motor extinction is introduced as a useful clinical measure of neglect-related movement difficulties and a significant clinical problem in its own right. CONCLUSION: Motor neglect is a relatively under-recognized deficit which may have a significant impact on patient performance and recovery following stroke. We conclude with a discussion of the implications of motor neglect for rehabilitation, including the relative contributions that may be made by Constraint-induced movement therapy and Bilateral movement therapy in managing patients with neglect-related movement problems.